Disinflation in Transition Economies : The Role of Relative Price Adjustment - Coorey, Sharmini (IMF Working Papers; Working Paper, 1996)
In light of the persistence of moderate inflation in many transition economies, this paper analyzes whether inflation resulted from insufficiently tight financial policies and wage pressures or from the protracted adjustment of relative prices. Using a new database for 21 countries, the effect of relative price variability on inflation is estimated within a framework controlling for nominal and real shocks. Money and wage growth were the most important determinants of inflation; relative price variability had a sizable effect at high inflation during initial liberalization and a small effect at moderate inflation. Cost recovery may contribute to variability, particularly in the advanced stages of the transition.